2020
DOI: 10.1080/21548331.2020.1724454
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization review of tramadol hydrochloride in a regional hospital in South Africa; findings and implications

Abstract: Background: Drug utilization reviews (DURs) can be used to promote rational prescribing and ensure compliance with standard treatment guidelines. In recent years, the use of tramadol hydrochloride (HCl) for pain has increased significantly across countries. We sought to determine prescribing patterns and use of tramadol in a Regional Hospital in South Africa to provide future guidance in view of increasing concerns with the prescribing of tramadol. Method: A prospective, quantitative and descriptive study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This is seen with the FDC of acetaminophen/ibuprofen in patients with moderate to severe postoperative dental pain where the combination provided greater and more rapid analgesia than comparable doses of either agent alone [56]. Besides this, FDCs of tramadol and paracetamol may be opioid sparing without sacrificing effectiveness, which is seen as important given some of the recent concerns with tramadol especially its potential for abuse [260][261][262][263]. In addition, a tramadol/paracetamol FDC can present a potential alternative to nonsteroidal anti-inflammatory drugs (NSAIDs) in the elderly reducing concerns with possible gastrointestinal side-effects [264].…”
Section: Painmentioning
confidence: 99%
“…This is seen with the FDC of acetaminophen/ibuprofen in patients with moderate to severe postoperative dental pain where the combination provided greater and more rapid analgesia than comparable doses of either agent alone [56]. Besides this, FDCs of tramadol and paracetamol may be opioid sparing without sacrificing effectiveness, which is seen as important given some of the recent concerns with tramadol especially its potential for abuse [260][261][262][263]. In addition, a tramadol/paracetamol FDC can present a potential alternative to nonsteroidal anti-inflammatory drugs (NSAIDs) in the elderly reducing concerns with possible gastrointestinal side-effects [264].…”
Section: Painmentioning
confidence: 99%
“…Relevant research had demonstrated that tramadol, rather than other more powerful opioid medications, can also have some desirable postoperative analgesic effects but with fewer side effects. [102][103][104] The Royal College of Anesthetists claims that 67 mg of tramadol offers the same analgesic effective as 10 mg of morphine. 105 Consequently, tramadol is often utilized in low-and middle-income nations.…”
Section: Medicine Shortage and Restrictionmentioning
confidence: 99%
“…105 Consequently, tramadol is often utilized in low-and middle-income nations. 104 However, the United National Office on Drug and Crime raised the alarm in its annual World Drug Report, stating "… about addiction to tramadol, rates of which are soaring in parts of Africa. This puts further strain on already overburdened healthcare systems".…”
Section: Medicine Shortage and Restrictionmentioning
confidence: 99%
“…As the use of opioids in these nations rises, so does the number of opioid-related deaths; this very much follows the experience of the United States. Problematic and nonmedical use of tramadol has been reported in Egypt [ 33 ], Ghana [ 34 ], South Africa [ 35 ], and other African nations [ 36 ].…”
Section: Reviewmentioning
confidence: 99%